2013
DOI: 10.1111/epi.12225
|View full text |Cite
|
Sign up to set email alerts
|

Comparative steady‐state pharmacokinetic evaluation of immediate‐release topiramate and USL255, a once‐daily extended‐release topiramate formulation

Abstract: SUMMARYPurpose: Compare the pharmacokinetic (PK) profiles of immediate-and extended-release formulations of topiramate (TPM) in healthy subjects following multiple dosing, and evaluate maintenance of topiramate exposures after switching formulations. Methods: A randomized, open-label, single-center, twoway crossover, multiple-dose study comparing the steady-state PK profile of once-daily extended-release topiramate (USL255) to immediate-release topiramate (TPM-IR) administered twice-daily. The TPM PK profile w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 30 publications
(40 reference statements)
1
28
0
Order By: Relevance
“…Patients were assessed over two 14-day maintenance periods, a crossover period, and 12-day titration period. 18 Although QXR and TPM-IR demonstrated equivalent steady-state, peak and trough exposures, QXR took more time to reach peak concentrations compared with TPM-IR (6 vs 1 h, respectively). QXR also had greater plateau time than TPM-IR (13 vs 4 h, respectively).…”
Section: Pharmacology Pharmacokinetics and Dosingmentioning
confidence: 93%
See 3 more Smart Citations
“…Patients were assessed over two 14-day maintenance periods, a crossover period, and 12-day titration period. 18 Although QXR and TPM-IR demonstrated equivalent steady-state, peak and trough exposures, QXR took more time to reach peak concentrations compared with TPM-IR (6 vs 1 h, respectively). QXR also had greater plateau time than TPM-IR (13 vs 4 h, respectively).…”
Section: Pharmacology Pharmacokinetics and Dosingmentioning
confidence: 93%
“…Source: Adapted with permission from John Wiley & Sons. 18 Wang et al 5 associated with both an increased ethinyl estradiol clearance and an 18% to 30% decreased ethinyl estradiol AUC. 26 Therefore, it would be prudent to use oral contraceptive pills having a higher estrogen content while on TPM 21 ⩾200 mg/ day and/or to use a different form of contraception.…”
Section: 7mentioning
confidence: 99%
See 2 more Smart Citations
“…USL255 [5]. In phase I studies, USL255 displayed equivalent drug exposure to TPM-IR, with a smoother concentration-time curve and an improved steady-state PK profile (e.g., reduced fluctuation index, significantly decreased maximum plasma concentrations) [6,7]. The recent PREVAIL phase III study demonstrated that USL255 significantly improved seizure control in adults with drug-resistant partial-onset seizures (POSs) taking one to three concomitant AEDs [8].…”
Section: Introductionmentioning
confidence: 99%